The enemies of Rome : the barbarian rebellion against the Roman empire - Kershaw, Stephen P (Pegasus Books, 2020)
A narrative history of the Roman Empire from the point of view of the "barbarian" enemies of Rome. Rome's history follows a remarkable trajectory from its origins as a tiny village of refugees from a conflict zone to a dominant superpower. But throughout this history, Rome faced significant resistance and rebellion from peoples whom it regarded as barbarians: Ostrogoths, Visigoths, Goths, Vandals, Huns, Picts and Scots. Based both on ancient historical writings and modern archaeological research, this new history takes a fresh look at the Roman Empire through the personalities and lives of key opponents during the trajectory of Rome's rise and fall.